The effect of communication strategy on the relationship between strategy execution (organisational level) and organisational performance: a middle level managers' perspective at higher education institutions - Siam, Mohammed R. A. (Inderscience Publishers, 2017)
This study aimed to analyse the effect of communication strategy on the relationship between strategy execution and organisational performance of universities.The proposed constructs of independent variables were organisational level of analysis (organisational size, organisational structure, organisational culture, and reward system), and communication strategy. Specifically, the communication strategy was tested as a moderator.In other words, the effects of these three constructs were measured against organisational performance. The study was developed based on general system theory and contingency theory.The total respondents were 236 and all of them are working with the higher education institutions in Palestine. Based on SEM-PLS to analyse the data, the study found that specific strategy execution with a specific communication strategy produced better organisational performance.Finally the findings provide invaluable implication to theory and practice on execution of strategy of service based institutions like universities.